Практическое применение психологии в сфере профориентации - Шестаков, В. А. (ХНУРЕ, 2019)
The given work is devoted to the modem approaches in phychology that able to categorize personalities and get career guidance based on invidual traits. Personality type only outlines tendencies because it is only one of many factors that guide our behavior. However, personality test can be applied for choosing professional path with high degree of accuracy.